In situ EDXRD measurement of the low transformation temperature effect in laser beam welded stainless steel - F Akyel; M Gamerdinger; K Mäde; K.R.Krishna Murthy; S. Olschok; R. Sharma; U. Reisgen; G. Abreu-Faria; G. Dovzhenko (Journal of Advanced Joining Processes, 2024)
This paper investigates the low-transformation-temperature (LTT) effect in austenitic high alloy stainless steel and its influence on strain evolution of laser beam welded specimen. Due to the local heat input high temperature gradients occur between weld seam and base material, which lead to thermal and transformation induced strains. With targeted alloying in the weld seam the martensitic phase transformation can be shifted to lower temperatures resulting in the so-called Low Transformation Temperature (LTT) effect. This effect uses the volume expansion during the martensitic phase transformation. The delayed volume expansion during martensite phase transformation introduces continuous compressive strains until room temperature is reached and represents a mechanism that can serve to counteract the tensile strains caused by thermal shrinkage. The martensitic microstructure is achieved by dissimilar welding, combining an austenitic stainless steel base material with low alloyed filler wire. With this, the chemical composition of chromium and nickel is diluted, and a martensitic phase transformation occurs. As comparison, similar material combinations of stainless steel base material and conventional welding consumable are performed. In this work, in situ energy-dispersive x-ray diffraction (EDXRD) measurements in the beamline P61A at DESY are performed to investigate the expansion behaviour of martensite based on spectral data. Nine measuring positions are recorded and the strain evolution during welding and cooling of the samples are analysed. It is shown that the martensitic phase transformation changes the strain behaviour and implements compressive strain depending on the distance to the laser spot. It is found that the effect is orientation-dependent and that the highest strain influence is present in welding direction.